An aggressive locoregional orbital rhabdomyosarcoma and Li Fraumeni syndrome - Erok, Berrin; Kıbıcı, Kenan (Wydawnictwo Uniwersytetu Rzeszowskiego, 2021)
Introduction. Rhabdomyosarcoma (RMS) is the most common pediatric soft tissue sarcoma with 10 % of the cases occuring in the orbit. Patients often present with a rapidly developing proptosis and globe displacement. Aim. We aimed to present a very rare presentation of orbital RMS, with a giant exophytic orbital mass, a very rare presentation occuring in more advanced cases. Description of the case. A 3-year old girl presented to our hospital with a rapidly enlarging tissue like ulcerative mass. Her past medical history was remarkable with the diagnosis of embryonal rhabdomyosarcoma (RMS) and treatment with chemoradiotherapy at the age of 15 months. On magnetic resonance imaging (MRI), there was a giant heterogenously enhancing mass filling the right orbit and extending to the intracranial region. Li Fraumeni syndrome (LFS) was considered due to her sister death from neuroblastoma at an early age. Cytogenetic analysis revealed mutations of p53 gene, which supported our consideration. Conclusion. RMS is a highly malignant tumor which usually occurs sporadiacally. However, some rare syndromes are associated with increased incidence of RMS, such as LFS.
Keywords: del17p13.1; giant orbital mass; Li Fraumeni syndrome; rhabdomyosarcoma